PING‐Mapper: Open‐Source Software for Automated Benthic Imaging and Mapping Using Recreation‐Grade Sonar. Issue 9 (8th September 2022) - Bodine, C. S.; Buscombe, D.; Best, R. J.; Redner, J. A.; Kaeser, A. J.
Abstract: The characterization of benthic habitats is essential for aquatic ecosystem science and management, but is frequently limited by waterbody visibility and depth. Recreation‐grade side‐scan sonar systems are increasingly used to aid scientific inquiries in aquatic environments due to their relative low‐cost, ease of operation, low‐weight, and ease of mounting on a variety of vessels. However, existing procedures and software for post‐processing these data are either limited, closed source, or fail on data from new sonar models, limiting the development of reproducible workflows. Here, we present PING‐Mapper, an open‐source and freely available side‐scan sonar post‐processing toolset for processing and mapping sonar recordings from popular Humminbird instruments. The modular software automatically: (a) decodes sonar recordings from any Humminbird system, (b) exports ping attributes from every sonar channel, (c) uses sonar sensor depth for water column removal, and (d) exports sonogram tiles and georectified mosaics. Sonar channels are processed in parallel for quick decoding and metadata extraction. Major processing wokflows, including georectification and image export, are optimized to scale with computing resources. The software has been extensively tested using data from several rivers of varying character and distribution of depths, but could also be used in estuarine and lacustrine environments. Usage of PING‐Mapper is illustrated in three case studies focused on mapping large woody debris, bathymetric mapping, and visual interpretation and mapping of substrates for selected reaches of the Pearl and Pascagoula river systems in Mississippi. Plain Language Summary: Side‐scan sonar instruments provide a way to survey and visualize the bottom of rivers, lakes, or oceans. Since the early 2000s, companies catering predominantly to anglers have manufactured recreation‐grade side‐scan sonar systems to aid fishermen in locating fish and identifying potential hazards. Scientists seeking to understand and manage aquatic habitats used these systems to create grayscale images of water bottoms because they are inexpensive, easy to operate, and require minimal mounting equipment on the boat. Software has been created by companies to process these data, but the underlying processing workflow and computer code are not publicly available, making it difficult to reproduce and compare results across studies. Other publicly available approaches and software are either outdated, not maintained, or not free. That is why we made PING‐Mapper, a freely available software developed in an increasingly popular programming language called Python. We designed the software to work on any computer to export the data sets quickly and efficiently. The scientific use of exported data sets is demonstrated with three case studies focused on locating and mapping targets (specifically large trees and branches), creating depth maps, and visually discerning the distributions of common substrates, such as sand and cobble. Key Points: We developed an open‐source software for exporting benthic data sets and georeferenced imagery from Humminbird side‐scan sonar systems Software provides an automated and reproducible approach to processing sonar data with minimal interaction from the user Three case studies are presented to highlight use cases of processed benthic data sets